Knowledge, perception and practice of breast self examination among daughter of breast cancer patient and daughter of non breast cancer patient, 1999 - Khalijah Mohd Yusof; Hanafiah Mohd Salleh (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Breast cancer is becoming more prevalent amongst women. In Malaysia, the incidence of the disease is approximately one half of that in the western world. It is also the third most common cause of death among cancer patients. The risk factors of breast cancer are identifiable such as family history, and breast self examination is an easy, cheap and effective method of early detection. A comparative cross sectional study was carried out at Radiotherapy Institute and Female Medical and Orthopedic Ward of Kuala Lumpur Hospital in June 1999 to determine the knowledge, perception and practice of breast self examination (BSE) among daughter of breast cancer patient and daughter of non breast cancer patient who are 15 years old and above. 169 questionaires were mailed to the breast cancer patient, out of which 70 daughters responded. 150 questionaires were handed to the non breast cancer patient in the ward, out of which 80 daughters responded. Overall response rate was 48 %. The study concluded that the level of knowledge and practice of BSE of daughters of breast cancer patient is better compared to the daughters of non breast cancer patient. Mean score of knowledge of breast cancer is 6.97 for daughter of breast cancer patient and 4.80 for daughter of non breast cancer patient. 84.3% of daughters of breast cancer patients perform BSE with 30.5% of them performing it monthly. For daughters of non breast cancer patients, only 45.0% do perform BSE with 27.5% of them practicing it monthly. Family history is the significant factor influencing BSE, whereby daughter of breast cancer patient is seven times more likely to perform BSE compared to daughter of non breast cancer patient (OR 6.65, 95%CI 2.23-19.82). Secondary education level is also significantly related to BSE practice. Perceived self confidence to perform BSE has significant relationship to BSE practice of daughter of breast cancer patient, while perceived barrier to perform BSE has significant influence to BSE practice of daughter of non breast cancer patient. In conclusion the level of knowledge must be improved with emphasis on the risk factors of breast cancer during health education in school or clinic. This will undoubtedly improve women's perception of BSE as well as enhancing their BSE practice